2012
DOI: 10.1111/j.2042-7158.2012.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics (CFD) assisted performance evaluation of the Twincer™ disposable high-dose dry powder inhaler

Abstract: CFD is a highly valuable tool for development and optimisation of dry powder inhalers. CFD can assist adapting the inhaler design to specific physico-chemical properties of the drug formulation with respect to dispersion and retention behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 18 publications
(40 reference statements)
0
24
0
Order By: Relevance
“…Recent studies demonstrated that the DPI formulation of jet‐milled CMS could achieve a FPF (<5 μm) of approximately 59%–67% of the loaded dose (10–50 mg) via a Twincer™ device which has a higher resistance than the Aerolizer® (0.0 4kPa vs. 0.018 kPa 0.5 min/L) . These studies used the milled CMS containing coarse lactose, whereas the present study used the spray‐dried colistin sulphate alone.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies demonstrated that the DPI formulation of jet‐milled CMS could achieve a FPF (<5 μm) of approximately 59%–67% of the loaded dose (10–50 mg) via a Twincer™ device which has a higher resistance than the Aerolizer® (0.0 4kPa vs. 0.018 kPa 0.5 min/L) . These studies used the milled CMS containing coarse lactose, whereas the present study used the spray‐dried colistin sulphate alone.…”
Section: Discussionmentioning
confidence: 93%
“…New DPI design and development will benefit from computer-aided design. CFD and discrete element method may assist optimizing the flow field and particle behavior inside, but also ex-mouthpiece of the inhaler into the oral cavity [173][174][175][176][177]. New 3D printing techniques facilitate rapid DPI prototyping and making casts of (upper) parts the respiratory tract based on high-resolution CT scans [178].…”
Section: Dry Powder Inhalation: Futurementioning
confidence: 99%
“…In the passive DPI devices field, there is still nothing commercially available to meet these dose requirements, although devices such as the Twincer Ò may be capable of reaching the low end (*50 mg) of these dose regimes. (12) The most immediate application of high-dose inhalation therapy is in the promotion of mucociliary clearance and treatment of local lung infection. Respiratory infection is the number one cause of death worldwide, (13) usually a consequence, albeit terminal, of other disease state, like chronic obstructive pulmonary disease and cancer, and results in bacterial or viral colonization in the lungs with associated hypermucosal secretion.…”
Section: Introductionmentioning
confidence: 99%